On certain quasi-complemented and complemented Banach algebras - Pak-Ken Wong (International Journal of Mathematics and Mathematical Sciences)
In this paper, we continue the study of quasi-complemented algebras and complemented algebras. The former are generalizations of the latter and were introduced in [4] and studied in [4] and [11]. Some results are proved.